ACCEPTING THE OTHER IN TEACHING FRENCH AS A FOREIGN LANGUAGE: THE CONTEXT OF THE CEF - Emaish, Nahed (European Scientific Journal, ESJ, 2015)
Researchers have always discussed the need for an efficient approach to teaching culture in languages. The intercultural approach is the dominant one today. This paper takes interest in the application of the intercultural approach to teaching French as a foreign language in Jordan. It presents a study conducted at the department of French at the University of Jordan and it shows the results of applying this approach in the classes of French civilization in two stages. It also discusses the position of the Common European Framework of Reference for Languages towards this approach. The forthcoming findings of the study may be used to improve teaching/learning processes in teaching foreign languages in Jordan.